Kitab Rukun Istinjak: Integration of Fiqh and Sufism in the Early 19th Century of West Borneo Hinterland - Faizal Amin (Universitas Islam Negeri Mataram, 2022)
Kitab Rukun Istinjak [Book on the Procedure for Cleaning the Private Parts after Relieving Oneself] is a manuscript that originated from interior Borneo of West Kalimantan in the early 19th century. The text describes the concepts of fiqh [Islamic jurisprudence], which provides not only technical explanations for the implementation of rituals but also a description of philosophical concepts for the consumption of the heart/soul. The context of the private collection of manuscripts is for a minimal audience, namely the sālik [follower of Sufism] who study and practice the teachings of Sufism in the way of Nūr Muḥammad [Light of Muhammad]. This Rukun Istinjak manuscript records Islamic teachings, which show the integration of Islamic jurisprudence into Islamic mysticism, which initially developed in hinterland Borneo. Even though the text indicates the existence of Sufistic-style Islamic teachings adopted by the indigenous Muslim community of West Kalimantan in the Putussibau area, in particular, there are no clues that explain their affiliation or relations with a specific tariqa order.